The Free and Informed Consent Statement and its Different Ways of Expressing the Research Subject’s Authorized Consent - Souza Leite Campinas, Lúcia de Lourdes; de Barros, Vera Lúcia (O Mundo da Saúde, 2006)
The Free and Informed Consent Statement (FICS) has as its main objective obtaining research subjects and/or their legal representatives consent for their voluntary participation in the research after they have received from researchers the clarifications on the following aspects of research: objectives, risks, procedures to be carried through — implying respect for the principles of confiden- tiality and secrecy. This article aims to reflect on the different forms the research subjects have for expressing their Free and Informed Consent. The authors report their experiences in obtaining subjects’ consent for research carried through with people from different cultures in Brazil northern region in institutional projects from São Camilo University Center — São Paulo between 1998 and 2003. It was observed that FICS was obtained in different ways, according to each community culture. One not always have the possibility of getting the subjects’ signature, as is the case of traditional cultures that are “oral” cultures, that is illiteracy due not only to exclusion regarding access to schooling but also to an special valuation of oral communication. Before the experiences lived in the research field, the authors made efforts to act according to ethicity, understood as the perception/conscience of the situation, the possibility of locating oneself in a balanced way between emotion and reason, and coherence in actions, the use of common sense.